The Efek Neuroprotektif Kafein terhadap Fungsi Motorik pada Penyakit Parkinson - Khairun Nisa Berawi; Ilham Nugroho (Jurnal Ilmu Medis Indonesia, 2021)
Background: Coffee is one of the most consumed drinks in the world and has become a routine part of everyday life. Coffee is known to be a stimulant because of its high caffeine content. Parkinson's disease is the second most common neurodegenerative disorder characterized by the clinical presentation of motor and non-motor disorders. Neuroinflammation plays a major role in the pathogenesis of Parkinson's disease which is regulated by reactive microglia and causes neurodegeneration of dopaminergic neurons. Consumption of caffeine can exert anti-inflammatory effects on nerves in a variety of pathological conditions. Method: The method used is a literature study from various national and international journals. This method is used with the aim of summarizing a current topic in order to increase an understanding. The literature study restates previously published material and reports new facts or analyzes from relevant literature studies and then compares the results in the article. Results: Caffeine can act as a neuroprotective against the development of Parkinson's disease by keeping the blood-brain barrier intact so that the function of the central nervous system remains stable. Caffeine can improve motor function in Parkinson's disease patients by modulating adenosine A2AR receptors at different doses. Caffeine as an adjuvant drug in the treatment of Parkinson's disease is given together with Trihexyphenidyl (THP) which is an anti-Parkinson's agent that has been used clinically to treat Parkinson's disease. Conclusion: Caffeine is a neuroprotective agent that is widely available and can be used in the treatment of Parkinson's disease with current therapies. However, the correct dosage and safety of caffeine are of particular concern, especially when given at high doses for a period of time and concurrently with other Parkinson's drugs.